SOCIALIZATION OF PLANT SACHA INCHI AS AN ANIMAL FEED INGREDIENT IN REULEUT TIMUR GAMPONG ACEH UTARA DISTRICT - Yusra; Mawardati; Hafni Zahara; Nasruddin; Ade Firmansyah Tanjung; Aprilian Hidayahsyah; Siti Salmah (RADJA PUBLIKA, 2022)
This plant is easy to cultivate so farmers can cultivate it and make it animal feed. This of course will make it easier for breeders because livestock do not have to be released and get enough feed. Planting sancha ichi plants can be a solution to the problems faced by people in this region because these plants can survive in any soil conditions. Besides being able to be used as a raw material for animal feed, this plant can also solve the problem of the impact of global warming in this area which is produced by brick factories around residents' residential areas. This community service activity is expected to solve the various problems above. The community service location was taken around the UNIMAL Faculty of Agriculture, namely Gampong Reulet Timur, North Aceh Regency. The implementation method used in this service activity is in the form of counseling and mentoring with a participatory approach and referring to the adult-learning process which consists of: (1) Presentation of material supplemented by Power Point presentations and simulation materials, (2) discussions with service participants, (3 ) assistance for the practice of cultivating/planting pythons and making animal feed. The output targets to be achieved from this activity are: (1) Scientific publication in cross-reference/national-based international service journals (2) Publication of activities in print or online media, (3) product of python inch.